Fear in the Classroom: Campus Carry at The University of Texas at Austin - Butters Albion M. (The University of Texas at Austin, 2025)
This article examines the significance of fear of concealed handguns in the classroom at a public university in Texas, analyzing perceived changes in shared social space and the collective learning environment in terms of affect. This multimethod study provides a framework for understanding the factors behind the fear, which may be seen as personal, societal, or a dynamic combination of those manifested in local relationships. Furthermore, it explores disruptions of instruction and discussion, the profiling of other students as potential gun carriers, and the introduction of situational awareness in class. Based on ethnography conducted at The University of Texas at Austin, where campus carry was implemented in 2016, this article provides a context for those in the discipline of education, as well as instructors and administrators at other institutions of higher learning in the United States, to consider the complex nature of fear of guns and its impact on the classroom atmosphere.